Persepsi Karyawan Mengenai Whistleblowing System terhadap Pencegahan Fraud dengan Perilaku Etis sebagai Variabel Intervening - Ismawijayanthi, Gusti Ayu Diah Laksmi; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Akuntansi, 2023)
This study aims to determine employee perceptions regarding whistleblowing towards fraud prevention through ethical behavior as an intervening variable. The sample in this study were all employees of PT. PLN (Persero) Bali Distribution totaling 822 people. Data analysis technique uses simple linear regression and path analysis. The results of the study show that employee perceptions of whistleblowing have a significant effect on fraud prevention, employee perceptions of whistleblowing have a significant effect on ethical behavior, ethical behavior has a significant effect on fraud prevention. Keywords: Whistleblowing; Fraud; Ethical Behavior